2020
DOI: 10.5694/mja2.50458
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of self‐reported non‐coeliac wheat sensitivity and gluten avoidance in Australia

Abstract: Objectives To determine the incidence of self‐reported non‐coeliac wheat sensitivity (SR‐NCWS) and factors associated with its onset and resolution; to describe the prevalence of factors associated with gluten avoidance. Design Longitudinal cohort study; analysis of responses to self‐administered validated questionnaires (Digestive Health and Wellbeing surveys, 2015 and 2018). Setting, participants Subset of an adult population sample randomly selected in 2015 from the electoral rolls for the Newcastle and Gos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
0
27
0
2
Order By: Relevance
“…Others avoided gluten for "general health" or as a treatment of abdominal pain, without being diagnosed with CeD or NCGS. The authors considered that gluten avoidance may be due to the current well-being trend and that NCGS may overlap with other gastrointestinal disorders [34]. Additionally, we observed that the NCGS group reported more gut symptoms per subjects when compared to CeD and healthy controls (p = 0.045).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Others avoided gluten for "general health" or as a treatment of abdominal pain, without being diagnosed with CeD or NCGS. The authors considered that gluten avoidance may be due to the current well-being trend and that NCGS may overlap with other gastrointestinal disorders [34]. Additionally, we observed that the NCGS group reported more gut symptoms per subjects when compared to CeD and healthy controls (p = 0.045).…”
Section: Discussionmentioning
confidence: 51%
“…This may be an indication that they are not aware of the composition of GFD. According to a recent survey study of Potter et al [34], 24% of responded Australians avoided gluten completely or partially, while 14% had self-reported non celiac wheat sensitivity and 1% had celiac disease. Others avoided gluten for "general health" or as a treatment of abdominal pain, without being diagnosed with CeD or NCGS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the factors associated with new wheat sensitivity were younger age, female sex, and having FD. All together, these data suggest that IBS was strongly associated with baseline (2015), while FD was associated with incident (2018) self-reported non-celiac wheat sensitivity [11].…”
Section: Symptoms Of Dgbi In Patients With Ncgsmentioning
confidence: 68%
“…Although a correct estimate of the prevalence of NCGS could be achieved only with the application of double-blind controlled studies, this would be unfeasible on a large scale. With these limitations in mind, and based on self-reported data only, the prevalence of NCGS has been claimed to range between 0.5% and 15% [2,4,5,[9][10][11]55]. The prevalence of NCGS is higher in the third to fourth decade of life and generally higher in women than in men [2,4], although, based on a single study, in children, the prevalence of NCGS was higher in males than in females [56].…”
Section: Epidemiologymentioning
confidence: 99%
“…As reported in this issue of the MJA , Potter and his colleagues examined the incidence of self‐reported NCGS, its resolution, and the association of each with functional gastrointestinal diagnoses in a general population sample of adults responding to two successive Digestive Health and Wellbeing postal surveys. About the same proportion of people reported NCGS in 2015 and 2018; 41% of those who reported NCGS in 2015 did not report it in the 2018 follow‐up survey.…”
mentioning
confidence: 99%